DESIGN OF LOCAL WISDOM-INTEGRATED ACEH SONGKET WEAVING-MAKING TEXTBOOKS - Erni Erni; Armaini Rambe; Halimul Bahri Halimul Bahri; Muhibbuddin Muhibbuddin; Novita Novita (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Riau, 2023)
Culture that is inherited hereditary and takes place in certain local areas is an invaluable heritage, one of which is the weaving culture in Aceh Besar District of Aceh Province. The lack of young generation’s interest to sustain weaving activity is concerned with the existence of Aceh Songket weaving, which contains various philosophical meanings in the future. Through education, it should be a relay to maintain the culture of weaving in Aceh Province so that it becomes the identity of the Aceh people. The research in this article aims to design and determine the feasibility of the media, practicality, and effectiveness of the Aceh Songket Weaving-making textbook media Integrated with Local Wisdom. The development of textbook media uses a 4-D development model. The results of the validity testing validated by material experts and media experts indicate a score of 91.5% in which the considered aspects are categorized as very valid, the practicality testing indicates 80% in the Practical category, and the effectiveness testing on students’ performance aspects indicates a score of 80 in the good criteria. Along with the data, it can be concluded that textbooks are feasible to use in learning.